Populism and Populists: the Evolution of a Paradigm Between Mexico and Russia - Picarella, Lucia (2018)
The article analyzes the populist tendencies that underlie the current complex political panorama, in particular referring to the Mexican and Russian case. Despite the difficulty of defining such an ambiguous phenomenon, it seems appropriate to consider the strong relations between populism and the processes of democratic degeneration that characterize different countries in the current world scenario. Through an initial historical reconstruction, the authors reflect on the evolution of the phenomenon over the centuries, losing much of its original connotation. An ideological involution that is transferred to the institutional sphere and that nowadays is presented in the form of hyperpresidentialism and an extreme personalization of politics. Assuming the undeniable differences between the two cases of study, the work considers how the Latin American reality as well as the Russian case can represent an exemplary case of the crisis of the traditional democratic scaffolding and the affirmation of a charismatic leadership, central nucleus of this new populist-plebiscitary dynamics.